Species of Ammothereva Lyneborg, 1984 (Diptera: Therevidae: Therevinae: Cyclotelini) from China - Liu, Si-Pei; Gaimari, Stephen D.; Yang, Ding (Zootaxa, 2012)
The genus Ammothereva Lyneborg, 1984 is recorded from China for the first time. Three species, A. nuda sp. nov., A. flavifemorata sp. nov. and A. brevis sp. nov., from Northwest China are described as new to science. A key to males of all species of Ammothereva is presented, along with a distribution map for the three Chinese species.